Reviews of "Best of Times? The Social Impact of the Celtic Tiger" - Carmen Kuhling
Review Symposium of "Best of Times? The Social Impact of the Celtic Tiger" Edited by Tony Fahey, Helen Russell, Christopher T. Whelan, Institute of Public Administration, Dublin, 2007, re-released in 2008 as Quality of Life in Ireland: Social Impact of Economic Boom, Springer.